2014
DOI: 10.5194/se-5-1319-2014
|View full text |Cite
|
Sign up to set email alerts
|

Microscale strain partitioning? Differential quartz crystallographic fabric development in Phyllite, Hindu Kush, Northwestern Pakistan

Abstract: Abstract. Spatially referenced quartz c axis fabrics demonstrate the preservation of multiple, distinct fabrics in a specimen collected from northwestern Pakistan. The overall fabric yielded by the specimen is dominated by a single population of quartz grains, while the fabric signatures of two other unique, spatially distinct populations are overwhelmed. It is these minor fabrics, however, that provide information on temperature of deformation (403 ± 50 • C), differential stress (8.6 + 2.6/−1.5 MPa to 15.0 +3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Larson et al. (2014) have reported a possible example of this. They presented peripheral c‐axis maxima close to the shear direction in a temperature condition much below that required for the activation of prism <c> and used the concept of flow partitioning to explain their observation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Larson et al. (2014) have reported a possible example of this. They presented peripheral c‐axis maxima close to the shear direction in a temperature condition much below that required for the activation of prism <c> and used the concept of flow partitioning to explain their observation.…”
Section: Discussionmentioning
confidence: 93%
“…Most natural mylonites are made of polyphase minerals in which the microscale rheology varies from one domain to another which facilitates flow partitioning. In fact, many authors have referred to flow partitioning qualitatively (e.g., Garcia Celma, 1982; Jerabek et al., 2007; Killian et al., 2011; Larson et al., 2014; Law, 1987; Lister & Price, 1978; Passchier, 1983; Pauli et al., 1996; Peternell et al., 2010) to explain observed c‐axis fabric variations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the LPO pattern or activity of certain slip systems of quartz can be temperature dependent (Schmid & Casey, 1986; Stipp et al., 2002; Toy et al., 2008) though it should be noted that quartz LPO patterns may be complicated by complex bulk flow patterns or strain partitioning process (e.g., Jeřábek et al., 2007; Larson et al., 2014). When combined with detailed microstructural observations, the quartz LPO distributions can be used as an additional line of evidence to make rough estimates about the relative deformation temperatures experienced by different rocks specimens (Kurz et al., 2002; Law, 2014; Passchier & Trouw, 2005).…”
Section: Ebsd Analysis Of Quartz and Titanitementioning
confidence: 99%